Pengaruh Current Ratio (CR) dan Debt To Equity Ratio (DER) Terhadap Return On Asset (ROA) Pada PT Kereta Api Indonesia (Persero) Tbk Periode 2014-2024 - Ami Apryani; Yulian Bayu Ganar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study analyzes the effect of the Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Kereta Api Indonesia (Persero) Tbk during the 2014–2023 period. The research method used is a quantitative approach with multiple linear regression analysis, t-test, F-test, and coefficient of determination. The data used is secondary data in the form of the company's annual financial reports. The population in this study is all financial reports of PT Kereta Api Indonesia (Persero) Tbk, while the research sample is the balance sheet and income statement for 10 years, namely the 2014–2023 period. The results show that, partially, the Current Ratio does not significantly influence Return on Assets, with a calculated t-value of 0.121 <t-table 2.22814 and a significance value of 0.907 > 0.050. Meanwhile, the Debt to Equity Ratio had a negative but insignificant effect on Return on Assets, with a calculated t-value of -1.328 < t-table 2.22814 and a significance value of 0.226 > 0.050. This study also found that simultaneously, both variables (Current Ratio and Debt to Equity Ratio) did not significantly influence Return on Assets, with a calculated F-value of 1.043 < F-table 4.46 and a significance value of 0.401 > 0.050. The coefficient of determination (R²) of 0.230 indicates that only 23% of fluctuations in Return on Assets can be explained by the Current Ratio and Debt to Equity Ratio, while the remaining 77% is influenced by other factors outside the research model.